2019
DOI: 10.23937/2474-3658/1510079
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seasonal Cattle Movement on Prevalence of Trypanosome Infections in Cattle in the Maasai Steppe, Tanzania

Abstract: Animal African Trypanosomosis is a Neglected Tropical Disease with significant impacts to pastoral community livelihoods. Our study sought to determine the influence of seasonal cattle movements on the prevalence of trypanosome infections in cattle in the pastoral areas of the Maasai Steppe. Identification of spatial and temporal dynamics of trypanosome infections in cattle is essential for designing effective control strategies. To identify potential hotspots of trypanosome transmission, we worked with 5 past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The area under study was identified, demarcated and different categories of LULC were classified using Google Earth Pro as suggested by Ngongolo et al (2019). The area has been monitored for the last 25 years, from 1995 to 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The area under study was identified, demarcated and different categories of LULC were classified using Google Earth Pro as suggested by Ngongolo et al (2019). The area has been monitored for the last 25 years, from 1995 to 2020.…”
Section: Methodsmentioning
confidence: 99%